Attitudes of Saudi Electronic University (SEU) Students in Riyadh toward Adaptive Learning - Bin Shalwan, May Saad; Al-abbasi, Daniah Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
This study was designed to explore the attitudes of the students of the Saudi Electronic University toward adaptive learning in Riyadh. The respondent sample included 326 students ranging in age from 18-35 years, where the descriptive survey approach was used to achieve the objectives of the study and to answer its questions using a customized questionnaire. The results showed positive attitudes of the Saudi Electronic University students towards the Education Frist (EF) system used for English course in the preparatory year. The recommendations were to increase technical support to solve the problems of adaptive learning system, and to provide training courses for students to explain how the system is used and train them on new updates.